Profiling Enterovirus and Parvovirus B19 in sudden and unexpected death in infancy (SUDI) at the Tygerberg Medico-legal Mortuary and the role of myocarditis as a possible cause of death - Saayman, Jamie Ester (Stellenbosch : Stellenbosch University, 2018)
Thesis (MMedSc)--Stellenbosch University, 2018.